URGENSI PERDA DALAM PENYELENGGARAAN OTONOMI DAERAH - Maryati Maryati (Jurnal LEX SPECIALIS, 2012)
Abstract Regulation is an inherent with the system of regional autonomy. Because the essence of local autonomy itself is independence and freedom or flexibility. Independence itself implies that the region has the right to organize and administer the affairs of the household own government. The authority set here means that the area has the right to make legal decisions such legislation later (among others) were named regional regulation.Regulation is an important instrument in the implementation of regional autonomy. because:1.With the principle of autonomy in Law. 32 of 2004, it is almost more government affairs diserak = respiratory to operate in areas that require a legally through legislation.2.Regulation as part of the national legislation, the implementation of autonomy in the regulation of blood is needed for further elaboration of the legislation is higher. Key Note : Autonomous Region, the Regional Regulation